O lesenih rogovih in rogistih na Slovenskem - Cvetko, Igor (Etnolog. Nova vrsta (Ljubljana), 2002)
Flutes and reed pipes of different types are certainly among the most popular aerophones in Slovenia. The range of Slovene folk instruments does not includemany wind instruments, but the most important among them are no doubt wooden horns. A wooden horn is made of a suitable branch which the maker firstcuts lengthways in two halves as accurately as possible, hollows out the central sections, and then glues them together again. The horn is then wrappedtightly in cherry bark. Wind instruments and horns, played by folk musicians to accompany dances, are mentioned in written sources as early as 15th century. Two centuries later a wooden horn is described in detail and documented in Valvasor's famous Die Ehre des Hertzogthums Crain (1686). Documentary ethnographic sources from the 18th, 19th, and 20th centuries mention, trace, search, and describe wooden horns. In 1996, Jože Setničar, an amateur trumpet player from Kresnice near Litija, started making wooden instruments, horns made of tree branches' two years later he founded his own ensemble called Leseni rogisti (The Wooden Hornists). The highly inventive horns he has made since are an interesting (and living) collection of original instruments.
Keywords: folk music; ljudska glasba; ljudska glasbila; trobila; Slovenia; Slovenija